Current State of the Field of Cell-Penetrating Peptides as an Honorific Issue for Professor Ülo Langel (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue entitled, initiated by the editorial team of Pharmaceutics, pays homage to Professor Ülo Langel for his remarkable scientific contribution to the field of cell-penetrating peptides (CPPs). Prof. Langel graduated from Tartu University, Tartu, Estonia, as a bioorganic chemist in 1974. He has obtained two PhD degrees: in 1980 from Tartu University, Tartu, Estonia (bioorganic chemistry), and in 1993 from Tartu University/Stockholm University (biochemistry/neurochemistry). Prof. Langel is a Professor at the Department of Biochemistry and Biophysics, Stockholm University, and at the Institute of Technology, Tartu University. Furthermore, he is an Associate Professor at The Scripps Research Institute, La Jolla, CA, USA and Honorary Professor at Ljubljana University, Slovenia.He has been an invited lecturer at numerous international conferences, and is a co-author of more than 450 scientific articles and 20 approved or pending patents. His main interest lies in neurochemistry, where his research is aimed at studying peptides, particularly neuropeptide receptors, and drug delivery via cell-penetrating peptides.